Rozwój kultury prawnej islamu – wprowadzenie do tematyki - Sadowa, Katarzyna; Kuriata, Agnieszka (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Undoubtedly, the Muslim culture is different in many aspects from European tradition. One of the main difference is the fact that there is no division of Muslim religious values and the law – in Muslim countries legal regulations are based on sharia. This may results in some controversies, especially with regards to Muslim minorities living in the Europe. As the percentage of Muslims in the European countries still increases, some analysis regarding sharia are worth to be conducted. Therefore authors present the main issues concerning sharia – law, as an introduction to more specific researches.
Keywords: szariat; prawo muzułmańskie; islam; prawo; Mahomet (prorok; \d ca 570-632)